2016
DOI: 10.1021/acs.jafc.6b00008
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Climate Factors on Soybean Protein, Oil Contents, and Composition by Extensive and High-Density Sampling in China

Abstract: From 2010 to 2013, 763 soybean samples were collected from an extensive area of China. The correlations between seed compositions and climate data were analyzed. The contents of crude protein and water-soluble protein, total amount of protein plus oil, and most of the amino acids were positively correlated with an accumulated temperature ≥15 °C (AT15) and the mean daily temperature (MDT) but were negatively correlated with hours of sunshine (HS) and diurnal temperature range (DTR). The correlations of crude oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 39 publications
8
63
1
Order By: Relevance
“…Average protein was lower (421 and 425 g kg −1 ) in the Guelph and Ridgetown programs, respectively, while oil was higher (200 and 204 g kg −1 ), compared with Guelph historical cultivars with 428 g kg −1 protein and 191 g kg −1 oil. The ranges of oil and protein values across the germplasm groups were similar to those reported in germplasm surveys, such as Qin et al (2014) with an oil range of 142 to 228 g kg −1 across 127 Chinese cultivars, and Song et al (2016) with an oil range of 142 to 240 g kg −1 across 763 Chinese cultivars. These two studies reported 318 to 498 g kg −1 and 312 to 498 g kg −1 protein, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Average protein was lower (421 and 425 g kg −1 ) in the Guelph and Ridgetown programs, respectively, while oil was higher (200 and 204 g kg −1 ), compared with Guelph historical cultivars with 428 g kg −1 protein and 191 g kg −1 oil. The ranges of oil and protein values across the germplasm groups were similar to those reported in germplasm surveys, such as Qin et al (2014) with an oil range of 142 to 228 g kg −1 across 127 Chinese cultivars, and Song et al (2016) with an oil range of 142 to 240 g kg −1 across 763 Chinese cultivars. These two studies reported 318 to 498 g kg −1 and 312 to 498 g kg −1 protein, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, Arabidopsis thaliana ecotypes that originate in cooler, mountainous regions of the world have lower levels of very long‐chain fatty acids compared to ecotypes from warmer, lower altitudes (Millar & Kunst, ). Recently, it was shown that soybean seeds maturing in warmer climates generally had higher levels of total fatty acid content with a decreased levels of linolenic acid and increased levels of oleic acid which correlated with mean daily temperatures, but not to maturity group (Song et al., ). In this study, we examined the lipid composition in seeds which had not been acclimated during maturation (all grown under similar constant and normal growth conditions) to identify any potential markers within fatty acid composition that could be used to predict cold/chilling germination success.…”
Section: Discussionmentioning
confidence: 99%
“…The climate data were obtained from the China Meteorological Data Sharing Service System (http://cdc.nmic.cn/home.do). The dates of the first flowering and full maturity for the 474 samples were provided by sample providers, and for the missing data refer to the study of Song et al 13 The details, which include accumulated temperature ≥ 15 ∘ C (AT 15 ), mean daily temperature (MDT), rainfall (RF), hours of sunshine (HS) and diurnal temperature range (DTR), are shown in Table 1.…”
Section: Climate Datamentioning
confidence: 99%